Evaluation of chitosan gel with 1% silver sulfadiazine as an alternative for burn wound treatment in rats - Nascimento,Ednaldo Gomes do (2009)
PURPOSE: Evaluation of the rheological, biological and therapeutic properties of a new topical formulation consisting of chitosan gel containing 1% silver sulfadiazine, as an alternative for the treatment of burn wounds. METHODS: An experimental study was done with 21 Wistar rats divided into three groups. Group I was treated with chitosan gel without the antimicrobial, group II was treated with chitosan gel with 1% silver sulfadiazine and group III was treated with commercially available 1% silver sulfadiazine cream. RESULTS: Due to its pseudoplastic characteristic and good bioadhesiveness, the chitosan gels showed a satisfactory retention time over the wounds. No statistical difference was found in the amount of drug released from the chitosan gel and commercially available cream, as well as in the healing time among the groups. Wounds treated with chitosan gel with silver sulfadiazine showed a higher fibroblast production and a better angiogenesis than in the other groups, which are important parameters on the evolution of the healing process. CONCLUSION: The topical use of chitosan gel in association with silver sulfadiazine ameliorated the neovascularization and inflammatory reaction in burn wounds. This new formulation showed advantageous rheological properties and efficient release of the drug.